IMPROVING MATHEMATICS LEARNING OUTCOMES OF CLASS VI STUDENTS THROUGH DISCUSSION METHOD AT BANYUAJUH 2 ELEMENTARY SCHOOL - Zairor Rizky Khanifah; Kusnaningsih Kusnaningsih; Rika Wulandari (maktab: Jurnal Pendidikan dan Teknologi, 2022)
One of the things that can affect the success of a lesson is the accuracy of the use of learning methods. The purpose of this study was to determine the increase in mathematics learning outcomes in the circle diagram material for class VI students at Banyuajuh 2 Elementary School through the discussion method. This research is a class action research conducted in 2 cycles. Data was collected through observation techniques, tests and documentation. The data that has been collected was then analyzed using descriptive quantitative qualitative data analysis techniques. The results showed that there was an increase in mathematics learning outcomes in the circle chart material for class VI students at Banyuajuh 2 School in each cycle. In cycle I, the average student learning outcomes in a classical manner is 63.6 with the percentage of students completing is 57%. Learning outcomes rose in cycle II to an average of 82.9 with the percentage of students completing 100%